Integrity Identification in Ethnographic by Biopic of Kwee Tjie Hoei - Rustono Farady Marta (Ikatan Sarjana Komunikasi Indonesia, 2018)
This research will specifically trace the communication made by Kwee Tjie Hoei (A Hoei) or Karmaka Surjaudjaja which is manifest in the national film titled with